Linkage of extracellular and intracellular control of cytosolic Ca2+ in rat osteoclasts in the presence of thapsigargin. - Zaidi, M; Shankar, V; Bax, C; Bax, B; Bevis, P; Pazianas, M; Alam, A; Moonga, B; Huang, C (1993)
Cytosolic [Ca2+] was measured in single osteoclasts using fura-2 in experiments investigating the effects of Ca2+ "receptor" activation using thapsigargin as a means of depleting intracellular Ca2+ stores. Application of 4 microM thapsigargin to osteoclasts in Ca(2+)-free solutions resulted in an elevation of cytosolic [Ca2+]. Under similar conditions, activation of the osteoclast Ca2+ receptor by the substitute divalent cation agonist, Ni2+, resulted in a transient elevation of cytosolic [Ca2+]. In both instances, restoration of extracellular [Ca2+] to 1.25 mM resulted in an "overshoot" of cytosolic [Ca2+]. Prior depletion of intracellular Ca2+ stores by thapsigargin markedly reduced the magnitude of the cytosolic [Ca2+] response to a subsequent application of 5 mM Ni2+. The application of 2 microM thapsigargin to intercept the falling phase of the Ni(2+)-induced cytosolic Ca2+ signal resulted in a sustained elevation of cytosolic [Ca2+], which was terminated by a second application of the same Ni2+. Furthermore, the sustained elevation of cytosolic [Ca2+] induced by thapsigargin application alone was abolished by late application of Ni2+. We conclude that activation of the surface membrane Ca2+ receptor on the osteoclast results in the cytosolic release of Ca2+ from intracellular storage organelles; the refilling of such stores depends upon a thapsigargin-sensitive Ca(2+)-ATPase; store depletion induces capacitative Ca2+ influx; and the Ca2+ influx pathway is sensitive to blockade by Ni2+.